Iowa Birdline update, December 13, 1993 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1993)
Email of the Iowa Birdline update for December 13, 1993. Highlights include large number of Gulls, including some that are rare in the state. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed